PENGARUH KEPEMILIKAN MANAJERIAL DAN KEBIJAKAN DIVIDEN TERHADAP KEBIJAKAN UTANG PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 - Diqa Hazna Widya; Ati Sumiati (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
The purpose of this research was to study the significant effect of Managerial Ownership and Dividend Policy to Debt Policy The Non-Financial sector on Listed Companies in Indonesian Stock Exchange in 2015. The method used is quantitative descriptive survey method with a descriptive and statistical analysis and regression approach. The research using the secondary data obtained from the reference center Indonesia Stock Exchange in 2015. Variable X as the independent variable is Managerial Ownership in measured by Managerial Ownership Ratio (MOWN) and Dividend Policy in measured by Dividend Payout Ratio (DPR). Meanwhile variable Y is proxied by Debt to Equity Ratio (DER). The sampling technique was conducted by random sampling. The attainable population in this research were all manufacture companies listed on the Indonesian Stock Exchange and the sample used by the computation Isaac Michael is 47 companies.The simple linier regression and resulted Å¶=0,780+0,018X1+0,122X2. The result of this research concluded that Managerial Ownership has not affect the Debt Policy where Thitung of Managerial Ownership is 0,625 smaller than Ttabel amounted to 2,000 and Dividend Policy in has positive and significant effect the Debt Policy where Thitung of Dividend Policy is 2,192 and Ttabel amounted to 2,000. In simultan. The Influence Between Managerial Ownership and Dividend Policy with Debt Policy is not significantly related. The ability of the Managerial Ownership and Dividend Policy explain Debt Policy is 10,30%. Keyword : Managerial Ownership, Dividend Policy, Debt Policy